2020
DOI: 10.1371/journal.pone.0236862
|View full text |Cite
|
Sign up to set email alerts
|

Measuring student motivation on the use of a mobile assisted grammar learning tool

Abstract: Language learning is an emerging research area where researchers have done significant contributions by incorporating technological assistantship (i.e., computer-and mobileassistant learning). However, it has been revealed from the recent empirical studies that little attention is given on grammar learning with the proper instructional materials design and the motivational framework for designing an efficient mobile-assisted grammar learning tool. This paper hence, reports a preliminary study that investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Responses are scored from 1 (not true) to 5 (very true), with no standard values set. The reliability of this questionnaire was Cronbach's α = .96 for the entire scale, .89 for attention, .81 for relevance, .90 for confidence, and .92 for satisfaction, 27 and it has been used in several studies 28–30 …”
Section: Methodsmentioning
confidence: 99%
“…Responses are scored from 1 (not true) to 5 (very true), with no standard values set. The reliability of this questionnaire was Cronbach's α = .96 for the entire scale, .89 for attention, .81 for relevance, .90 for confidence, and .92 for satisfaction, 27 and it has been used in several studies 28–30 …”
Section: Methodsmentioning
confidence: 99%
“…Learners also are found satisfied over the learning when graphics are used in the learning materials. Infographics and other elements such as pictures and diagrams help to improve learners' attention to the learning (Refat, Kassim, Rahman, & Razali, 2020) hence, elevate their motivation to move on learning.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Over the years, the ARCS model has been used to understand learners' language learning efficiency, and researchers found that students' achievement in English as Foreign Language was enhanced (Li et al, 2018); positively increasing their confidence, autonomy and learning motivation (Li et al, 2018;Refat et al, 2020).…”
Section: Arcs Motivation Modelmentioning
confidence: 99%